Exchange rate pass-through into German import prices - a disaggregated perspective - Ansgar Belke; Joscha Beckmann; Florian Verheyen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This study analyzes the exchange rate pass-through into German import prices based on disaggregated data taken on a monthly basis between 1995 and 2012. Our main contribution is twofold: firstly, we employ various time-series techniques to analyze data for different product categories, and also cointegration techniques to carefully distinguish between short-run and long-run pass-through coefficients. Secondly, in a panel data approach we estimate time-varying pass-through coefficients and explain their development with regard to various macroeconomic factors. Our results show that long-run pass-through is only partly observable and incomplete, while short-run pass-through shows a more unique character, although heterogeneity across product groups does exist. We are also able to identify several macroeconomic factors which determine changes in the degree of pass-through, which is especially relevant for policymakers.
Keywords: F41; F14; E31; 330